(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Over the last ten years, numerous companies have directed their attention toward “Total Quality Management (TQM)” as a plan to increase profitability, grow market presence, and strengthen competitiveness. Although TQM has shown achievement across industry, solutions, and the wider society category, several firms encountered difficulties in achieving their objectives, attributed to factors such as insufficient commitment from top management and neglecting customer-centric approaches. The present study aims to highlight and explore the benefits that arise from the implementation of TQM in organizational settings, and second, to conduct a detailed analysis of the understanding of "Quality" and the specific activities related to TQM within these organizations.